The Purposes, Practices, and Professionalism of Teacher Reflectivity / Insights for Twenty-First-Century Teachers and Students - Pultorak Edward G (Lanham, Maryland Rowman And Littlefield Education, 2010)
This book is an excellent resource for teacher educators who want to prepare teachers who can continue to learn in and from their practice and become better teachers throughout their careers. Introduction, Teacher Reflectivity in Theory and Research, Reflectivity within the Teacher Cycle: Promoting Prospective Teachers' Progress toward an Inquiry Stance, Purposes and Practices of Reflectivity in Teacher Development, The Nature of Reflection: Experience and Reflection and Action in a Preservice Teacher Literacy Practicum, Teacher Reflectivity in Teacher Education Programs, Outcomes of Teacher Education Portfolios' Impact on Reflective Thinking: A Review of Discourses, Teacher Reflectivity with Teacher Candidates, Teacher Reflectivity: Importance and Origins and Tools to Facilitate, Teacher Reflectivity in Schools and Classrooms, Using Reflective Journals to Close the Gap Between a Vision of Reform and Teaching Practice, The Role of Professional Teaching Standards in Teacher Reflection, Teacher Reflectivity and International Perspectives, Teacher Reflection: What it is and What it Does, Afterword.